Perception of local community towards sustainable homestay tourism in Bagan Sungai Burung, Perak - Quah, Kian Ming (2019)
Nowadays, tourism is growing rapidly and it plays a vital role in economic growth of Malaysia. During travel, accommodation such as homestay is a need for tourists. Thus, there are more local people who have become more motivated to run a homestay. However, some problems have been encountered by Bagan Sungai Burung village such as language barrier, limited rooms and not much of income generated during off-peak season. Hence, the main purpose of this study is to understand the perception of local community towards sustainable tourism in providing homestay program. A total of 200 locals were selected using purposive sampling technique. Descriptive analysis and multiple regressions analysis were used to analyse the data. The study found that the participation level of the local community in offering homestay records the highest mean score (M=3.75) on contributing towards the economy of local community at Bagan Sungai Burung village. The local community have positive perception towards sustainable homestay tourism because it contributes towards the economic development (M=4.22) of the local community as well as have positive impact on the environment (M=3.95) through various conservation efforts followed by social and cultural impact at (M=3.80) and (M=3.62) respectively. Informal education level, homestay engagement and supporting homestay program to become an important part of local community are the significant predictors in influencing the participation of local community in sustainable homestay tourism. The findings show that the amenities, training, promotion and funding of Bagan Sungai Burung village have to be improved.